COMMUNITY ADAPTATION STRATEGIES IN FACING CLEAN WATER SCARCITY IN NDETUZEA VILLAGE, NANGAPANDA SUB-DISTRICT, ENDE - Nurhaliza, Siti; Hasan, Muhammad Husain; Sukmawati (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
Detuzea Village is one of the locations in Nangapanda Sub-District, Ende Regency, which is affected by drought which causes clean water scarcity. in 2010-2016 water sources from dug wells and rivers experienced drought, causing the people of Ndetuzea Village to experience a clean water crisis to meet their daily needs. Then in 2018- 2020 some dug wells and also pam water owned by residents experienced drought. The purpose of this research is to find out how the form of adaptation strategies carried out by the community in dealing with clean water scarcity and to find out how the effectiveness of the adaptation strategies that the community does. The method used in this research is qualitative method, with data collection techniques using interviews, observation and documentation. The results showed that there were efforts from the community to deal with the water scarcity. Some of the efforts include, subscribing to community wells, subscribing to pam water and building water reservoirs. The preference of the Ndetuzea Village community for the adaptation carried out is quite effective because it has fulfilled the wishes and expectations of the respondents. Keywords: strategy, adaptation, scarcity, clean water, effectiveness